Does silence imply consent? Organ Donation and the Presumption of Informed Consent - Cárdenas Krenz, Arturo Ronald (2024)
In response to the global shortage of organ donation, each country has been applying different public policies to reduce the donor deficit. One of them has been to propose regulatory modifications to the presumed consent system, in order to establish a system in which a favorable will is presumed for post-mortem organ donation, unless the person has declared otherwise while alive. Recently, the Peruvian law has established the presumed consent system for the donation of organs; it means that, in the absence of express will, the donor's willingness to donate his or her organs at the time of death is now presumed. This regulatory modification follows a tendency established in other countries; however, others remain and respect the free and inform consent regards the willing of donating organs. This article presents a critical vision of this legal presumption. Under analyzing others health legal systems, we deveal the risks of violation of people's rights when applying a regulation in this sense, which establishes a kind of compelled solidarity, highlighting policies that promote organ donation without compromising fundamental rights.